Trace of evil [large type] - Blanchard, Alice (Blanchard, Alice. Natalie Lockhart series., 2020)
"Natalie Lockhart always knew she was going to be a cop. A rookie detective in Burning Lake, a town known for its dark past, she was raised on the wisdom of her chief-of-police father. Natalie uses these lessons and the scars of her past - a beloved sister, murdered as a teenager - to give families the closure she never got. Her task is to uncover the whereabouts of nine missing transients who have disappeared. One night, after a day of no leads, she offers a ride home to a fellow cop. What she sees next will unravel everything. Daisy Bruckner--beloved schoolteacher, wife to a cop, pregnant--is dead on her kitchen floor. A suspect almost comes to mind immediately--Riley Skinner, Daisy's student and one of the disenfranchised youths of Burning Lake. But it's not that simple. Riley is in a coma, collapsed only hours after her death. And Daisy had secrets of her own. Natalie knows there is more to this case, but as the investigation deepens, even she cannot predict the far-reaching consequences--for Daisy, for Burning Lake--and for herself. As the hunt for Daisy's killer ties in with the loose thread of her sister's murder, Natalie must use every skill she possesses to solve the crimes before her--and confront the darkest parts of herself. Spellbinding and haunting, Trace of Evil is a dazzling novel of twisting suspense and the effect of secrets left uncovered"--